KERJA SAMA IJEPA DALAM MIDEC (MANUFACTURING INDUSTRY DEVELOPMENT CENTER) PADA SEKTOR BAJA PERIODE 2008 - 2013 - Ibadurrohman Hanif, (2023)
This research discuss the cooperation conducted by Indonesia and Japan through IJEPA in the MIDEC scheme in the Steel sector. IJEPA itself is a bilateral economic cooperation conducted by Indonesia with Japan to increase trade and investment in Indonesia and Japan in which there are three main pillars, namely, trade liberalization, trade facilitation, and capacity building. MIDEC itself is one of the realizations in the implementation of IJEPA which is a manufacturing industry development center held with the aim to help improve the competitiveness of the industry and improve the quality of Indonesian industrial workforce in order to be able to compete and also be able to qualify to enter the Japanese market. Steel is one of the sectors involved in the MIDEC scheme because the Steel sector itself is one of the important sectors because for steel itself has a connection with the sub-sector industry as a raw material. Therefore, the MIDEC scheme itself is expected to provide good results in its implementation to help improve the quality of Indonesia's industry, especially in the Steel sector. This research uses descriptive qualitative research method with the aim to know and analyze the implementation of capacity building programs through MIDEC scheme in Steel sector. The theory and concept of bilateral economic cooperation, EPA, capacity building, and technology transfer are also used as instruments in conducting this research. In this case, Indonesia and Japan have agreed on several activities or programs to be carried out, but in the realization of cooperation conducted by Indonesia with Japan in the MIDEC scheme in the Steel sector has not run optimally because there are several obstacles in process of realizing its activities.